Consideration of Climate Impact on Used Colors in Residential Architecture of Humid and Hot Regions - Mehrabi, Mehdi (Journal of History Culture and Art Research, 2017)
Consideration of architecture in humid and hot climate shows a beautiful and efficient intelligence in the back of architecture body. Fine arts would be considered from different perspectives in the issue of their color choice. Consideration of climate impact on used colors in residential architecture of humid and hot regions is the purpose of this writing. Descriptive approaches are used to understand theoretical history of the investigated subject in traditional architecture by applying objective observations. In addition, reasons of color choice on residential buildings in humid and hot environments are elaborated. While each color values next to other colors, companionship of different colors creates beautiful colorful contrast in little area with relative wide cob materials (middle brown). In addition, pacifying colors also are another reason for this mater. The results suggest that the beauty concept has the most important impact on traditional settlements of humid and hot regions.